The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acsomega.7b01250
|View full text |Cite
|
Sign up to set email alerts
|

CdS QDs-Decorated Self-Doped γ-Bi2MoO6: A Sustainable and Versatile Photocatalyst toward Photoreduction of Cr(VI) and Degradation of Phenol

Abstract: In this work, CdS quantum dots (QDs)-sensitized self-doped Bi 2 MoO 6 has been synthesized using glucose as reducing agent by hydrothermal method, followed by in situ deposition of the QDs. The synthesized catalyst has been employed to reduce toxic Cr(VI) and degrade phenol from the aqueous solution. The structural, optical, and electrochemical characterizations are performed using X-ray diffraction, UV–vis diffuse reflection, photoluminescence (PL), scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 40 publications
0
42
0
Order By: Relevance
“…The HRTEM images further confirmed the anchoring of Co 3 O 4 QDs on CNNS nanosheets and demonstrated the formation of Co 3 O 4 /CNNS heterojunction, in which the particle size of Co 3 O 4 QDs was centered at ≈2.2–3.2 nm, matching well with the statistical particle size distribution diagram (Figure F–H). That is, the particle size of Co 3 O 4 QDs is small enough to exhibit the quantum confinement effect . Moreover, the distances of ≈0.200 and ≈0.243 nm correspond to the (400) and (311) planes in the spinel Co 3 O 4 lattice, respectively (Figure H) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HRTEM images further confirmed the anchoring of Co 3 O 4 QDs on CNNS nanosheets and demonstrated the formation of Co 3 O 4 /CNNS heterojunction, in which the particle size of Co 3 O 4 QDs was centered at ≈2.2–3.2 nm, matching well with the statistical particle size distribution diagram (Figure F–H). That is, the particle size of Co 3 O 4 QDs is small enough to exhibit the quantum confinement effect . Moreover, the distances of ≈0.200 and ≈0.243 nm correspond to the (400) and (311) planes in the spinel Co 3 O 4 lattice, respectively (Figure H) .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the distances of ≈0.200 and ≈0.243 nm correspond to the (400) and (311) planes in the spinel Co 3 O 4 lattice, respectively (Figure H) . Obviously, high crystallinity and ultrasmall particle size will accelerate photogenerated carrier to diffuse toward the surface, thus enhances its photocatalytic activity . Furthermore, both Co 3 O 4 QDs and CNNS are in tight contact with each other to form heterojunction in the interfacial area, which can efficiently retard the photogenerated electron/hole recombination and enhance the possibility of photogenerated charge participating in AOPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] They demonstrated that incorporation of CdS QDs into BiOI microplates (up to 4wt%)c ould improve the photocatalytic efficiencies to al arge extent. The enhanced performance was attributed to increased visible absorption and the significant separation of electron-hole pairs over CdS/BiOI type-II heterostructures.P arida and co-workers [16] designed CdS QD decorated self-doped Bi 2 MoO 6 nanocomposites and demonstrated their superior photocatalytic performance toward the degradation of phenol and fast reduction of toxic Cr VI .T he 3% CdS QD sensitized self-doped Bi 2 MoO 6 sample displayed Am agnetically separable Fe 3 O 4 @CdS type-II core-shell nanohybrid (NH) photocatalyst, with excellent antibacterial properties and photocatalytic activity,w as synthesized and characterized by means of structural, elemental, and morphological analyses. Steady-state and time-resolved emission and absorption spectroscopyw ere also exploited to realize the location of chargecarrier wave functions in the NHs.…”
Section: Introductionmentioning
confidence: 98%
“…The enhanced performance was attributed to increased visible absorption and the significant separation of electron–hole pairs over CdS/BiOI type‐II heterostructures. Parida and co‐workers designed CdS QD decorated self‐doped Bi 2 MoO 6 nanocomposites and demonstrated their superior photocatalytic performance toward the degradation of phenol and fast reduction of toxic Cr VI . The 3 % CdS QD sensitized self‐doped Bi 2 MoO 6 sample displayed the highest efficiency, namely, 47.5 and 97 %, toward the degradation of phenol and reduction of Cr VI , respectively, under solar light.…”
Section: Introductionmentioning
confidence: 99%